Classroom Interaction Among English Teacher And High Achiever Students’ At SMA IT IQRA Kota Bengkulu - Endang Haryanto; Rahmat Aji Septiyono (AL LUGHAH, 2020)
Based on interaction theory, classroom interaction between teacher and students is very important in supporting students’ achievement. Therefore, the purpose of this research was to find out how the classroom interaction between English teacher and high achiever students. The method of this research is qualitative and the subjects of research were the two high achiever students of XI IPS 2 classroom. The results of this research show that the collaborative learning method was applied by the teacher in the teaching learning process. During the implementation the method the teacher teaches the students by giving a topic to be discussed and the teacher facilitates the students by allowing the use all media which relates to topics such as mobile phones, books, internet accessing to discuss the topics given. The data shows that it creates the good classroom atmosphere so all students looked motivated and confidence. However high achiever students looked more active answering the questions and perform in front of the class